PERANCANGAN SISTEM INFORMASI PENGELOLAAN PEMASARAN, PEMESANAN DAN PENJUALAN AIR ISI ULANG SYIFAQUA: PERANCANGAN SISTEM INFORMASI PENGELOLAAN PEMASARAN, PEMESANAN DAN PENJUALAN AIR ISI ULANG SYIFAQUA - Agustira, Felia; Elisa, Erlin (LPPM Universitas Putera Batam, 2023)
Today's increasingly fierce business competition requires a company to operate with strategies that are relevant to the changing times. This sharp global competition is faced by many companies, this is a sign that the increasingly rapid business growth encourages each company to always provide the best to achieve company goals. Companies must be more competitive in optimizing the management of all company resources, both in financial management, production, marketing, and human resources. This is done to produce something of value and be able to meet consumer needs and desires. The research method was carried out using the waterfall method with the process being carried out as follows. The information system installed at the current Syifaqua Depot that is being built can help increase sellers or orders and transactions online. This system makes it easy for customers to get information about the gallons of water they want to buy whether available or not and the price of the gallons of water. According to the analysis and design of this information system which has been carried out by researchers, there are several tips for this research, namely in further research it is hoped that the system can be further developed, and the website menus can be added or developed to make Android more attractive and effective.